Biodiversity priority areas and conservation strategies for seed plants in China - Yang, Xudong; Zhang, Wendi; Qin, Fei; Yu, Jianghong; Xue, Tiantian; Huang, Yunfeng; Xu, Weibin; Wu, Jianyong; Smets, Erik F.; Yu, Shengxiang (Frontiers in Plant Science, 2022)
China is known for its abundant plant resources, but biodiversity conservation faces unprecedented challenges. To provide feasible suggestions for sustainable conservation, we used the species richness algorithm and complementary algorithm to study distribution patterns of 34,082 seed plants based on 1,007,196 county-level distribution records. We reconstructed a phylogenetic tree for 95.35% of species and estimated the spatial phylogenetics, followed by correlation analyses between different distribution patterns. We identified 264 counties concentrated in southern and south-western mountainous areas as hotspots which covered 10% of the land area of China and harbored 85.22% of the Chinese seed plant species. The biodiversity conservation priorities we identified were highly representative as we have considered multiple conservation indicators. We evaluated the conservation effectiveness and gaps in the network of nature reserves and identified 31.44, 32.95, and 9.47%, respectively, of the hotspot counties as gaps in the national nature reserves, provincial nature reserves and both together, with respectively 55.77, 61.53, and 28.94% of the species. Analysis of the species composition showed there were a large number of threatened and endemic species occurring in the nature reserves’ gaps. The conservation gaps need to be filled by establishing new nature reserves or national parks, especially in south-western China, and more attentions should be paid to strengthen the conservation of specific plant taxa due to the apparent mismatches between different distribution patterns.